2008
DOI: 10.1002/rnc.1340
|View full text |Cite
|
Sign up to set email alerts
|

Linear parameter varying control of wind turbines covering both partial load and full load conditions

Abstract: SUMMARYThis paper considers the design of linear parameter varying (LPV) controllers for wind turbines in order to obtain a multivariable control law that covers the entire nominal operating trajectory.The paper first presents a controller structure for selecting a proper operating trajectory as a function of estimated wind speed. The dynamic control law is based on LPV controller synthesis with general parameter dependency by gridding the parameter space.The controller construction can, for medium-to large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 29 publications
0
83
0
11
Order By: Relevance
“…Operating points are chosen based on Refs. [7,22]. K 0 is the controller at operating point (18 m/s, 14.92 deg) and K 1 is the linear controller at operating point of (19 m/s, 16.23 deg) with rated generator torque for full load operation of wind turbine.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Operating points are chosen based on Refs. [7,22]. K 0 is the controller at operating point (18 m/s, 14.92 deg) and K 1 is the linear controller at operating point of (19 m/s, 16.23 deg) with rated generator torque for full load operation of wind turbine.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Nonlinear state feedback torque control was used [5] for the above-rated power operating condition of wind turbine and DOBC strategies were reviewed [6]. Ostergaard et al observed that the operation of wind turbines at different wind speeds require some kind of gain scheduling, so they have applied linear parameter varying control to develop robust controllers that cater for a both partial load and full load conditions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, se debe incluir el mecanismo controlado que permite orientar el ángulo β de las aspas, a partir de la consigna β ref , ver figura 1. Este sistema de orientación puede ser impulsado por un actuador eléctrico o hidráulico, el cual se puede representar por la siguiente función de transferencia, según el trabajo reportado por (Ostergaard et al, 2008): (26) donde T β es el parámetro que define el tiempo de respuesta del sistema de orientación utilizado, mientras que K β es la ganancia de su controlador. Entonces el modelo lineal admite la siguiente representación matricial:…”
Section: Matriz De Funciones De Transferenciaunclassified
“…Diversas técnicas de control multivariable se han implementado en los aerogeneradores, como son: Control con Variación Paramétrica Lineal (Ostergaard et al, 2008), H ∞ (Rocha y Martins, 2003), Adaptativo (Johnson et al, 2008), Óptimo LQG (Selvam et al, 2009), PID descentralizado (Wu et al, 2008), Predictivo (Yang et al, 2009), Lógica Difusa (Simoes et al, 2009) y Redes Neuronales (Li et al, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation